Sony A7 III : pocket guide : buttons, dials, settings, modes, and shooting tips. (Rocky Nook, 2023)
Designed for photographers who haven’t memorized every button, dial, setting, and feature on their Sony a7 III, Rocky Nook’s handy and ultra-portable quick reference Pocket Guide helps you get the shot when you’re out and about.